2015
DOI: 10.1007/s10876-015-0891-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Structural Characterizations of Co-based Heusler Nanoparticles Fabricated via Simple Co-precipitation Method

Abstract: Nanoparticles of Co 2 FeAl magnetic alloy was successfully fabricated in the presence of a well-known capping agent, polyvinyl alcohol, as a polymer template. The magnetic properties were studied using hysteresis curve and firstorder reversal curve (FORC) measurements at room temperature. FORC diagrams demonstrated a wide distribution of the coercive field owing to the presence of different particle sizes in products. TEM image also showed that the synthesized samples are composed of some large clusters contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…8 and 9. Pezeshki-Nejad et al 52 and Alikhanzadeh-Arani et al 53 showed that for Co 2 FeAl nanoparticles, a decrement in size results in decrement in M s which is in agreement with our observations. The decrement in the M s with decrement in crystallite size can be interpreted using the core-shell model for nanoparticles, which divides the nanoparticle of size d into a ferromagnetic core and magnetically dead layer (or shell) of thickness t on its surface, 54 i.e.,…”
Section: Resultssupporting
confidence: 93%
“…8 and 9. Pezeshki-Nejad et al 52 and Alikhanzadeh-Arani et al 53 showed that for Co 2 FeAl nanoparticles, a decrement in size results in decrement in M s which is in agreement with our observations. The decrement in the M s with decrement in crystallite size can be interpreted using the core-shell model for nanoparticles, which divides the nanoparticle of size d into a ferromagnetic core and magnetically dead layer (or shell) of thickness t on its surface, 54 i.e.,…”
Section: Resultssupporting
confidence: 93%
“…(full-Heusler) or XYZ (half-Heusler), where X and Y are usually transition elements such as Ni, Co, Fe, Pd, Cr, and Z is an sp element such as Si, Al, Ge [1][2][3]. So far, several reports on the use of half-metallic Cobased full-Heusler alloy electrodes in magnetic tunnel junctions have been presented [4], synthesizing by different techniques, including conventional dc sputtering [5], ion beam sputtering [6], low-temperature molecular beam epitaxy [7], electrodeposition [8], arc melting method [9,10] and melt-spinning process [11].…”
Section: Introductionmentioning
confidence: 99%